Campylobacter fetus in Abomasal Fluid from Spontaneously Aborted Bovine and Ovine Fetuses - Merker Breyer, Gabriela; Dias, Maria Eduarda; Henker, Luan Cleber; Lorenzett, Marina Paula; Ferreira Baumbach, Leticia; Canal, Cláudio Wageck; Petinatti Pavarini, Saulo; Maboni Siqueira, Franciele (Acta Scientiae Veterinariae, 2021)
Background: Pregnancy losses are a major concern in livestock industry due to their economic impact on producers. Campylobacter fetus subspecies fetus (Cff) and C. fetus subspecies venerealis (Cfv) are directly related to reproductive failures in ruminants. Cff colonizes the gastrointestinal tract of a wide range of hosts leading to abortion, while Cfv is restricted to genital tract being generally associated to infertility in bovine. Considering the great economic losses related to campylobacteriosis in cattle and ovine herds, this study aims to investigate the occurrence of C. fetus, considering Cff and Cfv subspecies, in bovine and ovine spontaneously aborted fetuses in state of Rio Grande do Sul, Brazil. Materials, Methods & Results: In this study, samples of abomasal fluid collected from 30 spontaneously aborted bovine (n = 18) and ovine (n = 12) fetuses were investigated for the detection of Campylobacter fetus throughout conventional PCR. Positive fetuses for C. fetus presence were further analyzed by molecular assays for Cff and Cfv detection, in order to determine subspecies identification. When available, samples of the main organs of the thoracic and abdominal cavities, as well as the brain, skeletal muscle, eyelid, skin, and placenta were collected for further histopathological analyses and bacterial culture, aiming to assess the presence of infection lesions and pathogens in those sites, respectively. Additionally, RT-qPCR assays were also performed for the detection of ruminant pestivirus, in order to detect bovine viral diarrhea cases. Throughout the present methodology, C. fetus was detected in the abomasal fluid samples of 2 bovine fetuses, being both identified as Cfv subspecies by PCR. Histopathological analyses demonstrated that macroscopic and microscopic changes found in the Cfv-positive animals were not either specific or directly related to Campylobacter infections. Moreover, no significant bacterial growth was observed in microbiological culture from the collected tissues, and both fetuses were negative for ruminant pestivirus. Differently, there was no detection of C. fetus in any of the analyzed ovine fetuses. Discussion: Considering that abortion diagnosis rates reported in cattle and sheep industry are highly variable among the published studies, and that abortion diagnoses are commonly inconclusive due to difficulties in sampling methodology and inadequate identification of the pathogen involved, it is important to investigate the etiological causes of abortion the herds for better understanding the causes of pregnancy issues and monitoring their occurrence. In addition, the absence of pathognomonic lesions in the tissues investigated in the histopathological analyses observed in this study strongly suggests that well-known etiological agents commonly associated to abortion, such as Leptospira spp., Toxoplasma spp., Chlamydia spp. and Neospora caninum, are unlikely to be the cause of infection of the analyzed fetuses. Taking this into account, the presence of C. fetus in the abomasal fluid samples from two bovine fetuses demonstrated in the present study suggests the possible association of Cfv not only with infertility, but also with cases of bovine abortion, highlighting the importance of investigating unusual causal agents of abortions in sheep and cattle. Overall, an adequate diagnosis is essential for establishing better prevention strategies to avoid the circulation of abortion-related infectious agents in the herds. Keywords: campylobacteriosis, molecular diagnosis, venereal disease, abortion, reproductive disease.